SIMSON PEMIMPIN YANG JATUH DI FASE KEMAKMURAN: SEBUAH REFLEKSI TEOLOGIS BAGI KEPEMIMPINAN GEREJA - Simon, Simon; Setiawan, Tjutjun; Panggarra, Robi (BONAFIDE: Jurnal Teologi dan Pendidikan Kristen, 2024)
This article focused on Samson's fall when he was in the phase of prosperity and glory. The downfall in this article referred to engaging in sexual sin, corruption, abuse of power and various scandals. The portrait of Samson's fall narrated by the Book of Judges also happened to some spiritual leaders today. The background of the problem accompanied by factual data was the main basis of this article. In writing this article, literature study and hermeneutic approaches were used to design the articles. The formulations of questions asked were what caused Samson's fall in the prosperity phase? And why did church leaders tend to fall in their phase of prosperity? The findings of this article revealed that Samson fell because he was a leader who tended to be difficult to accept advice from others, he was individualistic, narcissistic, and easily swayed by lust. These things were not much different from the downfall of some spiritual leaders today, as a result the image of religious leaders was damaged because of their deeds.